Pengembangan Aplikasi SPMI Berbasis Web Untuk Monitoring Tri Dharma Dan Audit Mutu Internal Di Universitas Cipasung Tasikmalaya - Miftahudin Miftahudin; Nana Supiana; Alam Alam; Rafi Hafizmi Anggia; Windriyana Windriyana (Management of Information System Journal, 2026)
The monitoring process of the Tri Dharma Perguruan Tinggi (Three Pillars of Higher Education), learning monitoring, and Internal Quality Audit (AMI) at Cipasung University, Tasikmalaya, is still carried out manually, so data management and quality evaluation processes have not been running optimally. This study aims to develop a web-based Internal Quality Assurance System (SPMI) application that can support the monitoring and quality management process in a more integrated manner. The research method used is the Prototype method with the stages of needs analysis, system design, prototype development, and system testing. The application is designed using the Laravel framework and MySQL database. This study also applies RabbitMQ as a message broker to support asynchronous data communication between system modules. The main features of the application include Semester Learning Plan (RPS) management, research monitoring, Community Service (PKM), Intellectual Property Rights (IPR), and Internal Quality Audit (AMI) management. Testing results using the blackbox testing method indicate that all main features of the system can run according to user needs. The novelty of this study lies in the application of RabbitMQ in the web-based SPMI system to support the monitoring process and information distribution more quickly and integratedly.